Anemia in Brazilian pregnant women before and after flour fortification with iron - Fujimori, Elizabeth; Sato, Ana Paula Sayuri; Szarfarc, Sophia Cornbluth; Veiga, Gloria Valeria da; Oliveira, Valterlinda Alves de; Colli, Célia; Moreira-Araújo, Regilda Saraiva dos Reis; Arruda, Ilma Kruze Grande de; Uchimura, Taqueco Teruya; Brunken, Gisela Soares; Yuyama, Lucia Kiyoko Ozaki; Muniz, Pascoal Torres; et al. (Revista de Saúde Pública, 2011)
OBJECTIVE: To compare prevalence of anemia and hemoglobin (Hb) levels in Brazilian pregnant women before and after flour fortification with iron. METHODS: A repeated cross-sectional panel study of public health care centers of municipalities in the five Brazilian regions was conducted. Retrospective data were obtained from 12,119 medical records of pregnant women distributed in two groups: before fortification (delivery prior to June 2004) and after fortification (date of last period after June 2005). Anemia was defined as Hb